Pelatihan Penggunaan Peralatan Biologi dan Metode Pengukuran Faktor Lingkungan Bagi Guru dan Siswa di SMP Negeri 12 Ambon - Monalisa Pertiwi Jeriska Taihuttu; Handy Erwin Pier Leimena; Evelin Tuhumuri; Cecelia Anna Seumahu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
One of the recurring challenges in aligning instructional materials with laboratory activities is the limited information and knowledge that teachers possess regarding the use of science laboratory equipment and materials. Teachers’ inability or insufficient skills in operating laboratory instruments and utilizing laboratory materials appropriately can directly affect the effectiveness of practical sessions. The objective of this community service program was to train teachers and students at SMP Negeri 12 Ambon in the use of laboratory equipment, particularly for measuring environmental factors. This community engagement activity was conducted on 6 November 2024 at SMP Negeri 12 Ambon (Figure 1), involving a total of 52 participants. The methods employed included lectures and demonstrations. The lecture method was used to introduce various instruments available in the biology laboratory and to provide explanations regarding the functions and applications of each tool. The results indicate that both teachers and students were able to master the use of environmental measurement instruments and understand the basic principles of measuring environmental factors such as dissolved oxygen (DO), water pH, salinity, temperature, and geographical position.